Stepping into the Digital Era: Transformation of School Administration Efficiency and Educational Management through the Role of Information Technology - Urath, Samuel (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The rapid development of information and communication technology has had a significant impact on various sectors, including education. Innovations such as database management systems, e-learning platforms, and administrative applications have become integral parts of modern school administration. This research aims to explore the strategies and challenges in stepping into the digital era in the context of education, as well as offer insights into how information technology can be effectively implemented to enhance administrative efficiency and educational management. This research method employs a qualitative approach with a focus on literature review and descriptive analysis. Data for this research were obtained from Google Scholar with a range of years from 2019 to 2024. The author searched for articles in reputable academic journals relevant to the research topic including digital era, school administration, education management, information technology. Initially, 50 articles were identified, but through rigorous selection based on relevance and quality, 34 articles most appropriate for this dissertation were utilised. The study results indicate that the transformation of school administration efficiency and educational management through information technology is a necessity in this digital era. The role of information technology is not only as a tool but also as a primary catalyst driving fundamental change in education. The adoption of technology-based school and education management systems, administrative processes become faster, more efficient, and accurate.